Utilizing Crowdsourcing in Education: Academic Retiree and Professional Continuity - Raus, Mohd. Ikhsan Md.; Supian, Suzaini Harmiruslin; Zolkefley, Mohd Khairul Ikhwan Bin; Aziz, Muhd Eizan Shafiq Abd (Springer, 2019)
The socioeconomic challenges caused by aging populations have encouraged many countries to reevaluate the place of the elderly in society as well as to adopt measures in encouraging them to be participative. In recent decades, crowdsourcing has been identified as a rapid growth of innovative Internet-based information and communication technologies in giving the opportunities to educational organizations to reach their goals. With their accumulated skills and knowledge, academic retirees can be resourceful to society. However, their knowledge and experiences seem to be undervalued and underutilized. Retired academics have better opportunity to extend their contribution in the society as their valuable knowledge is more appreciated than people from other background. Retired academics tend to be able to fulfill their desire for professional continuity following retirement more markedly than people from other backgrounds. This paper analyzes the use of crowdsourcing in educational activities, especially for the academic retirees. Therefore, the objectives of this paper are to take an exploratory look on how educational organizations use crowdsourcing as part of their activities at the present time, and to suggest how the practice of crowdsourcing may expand to other educational activities in future.
Keywords: Asie; Réservé UdeM

Utilizing Crowdsourcing in Education: Academic Retiree and Professional Continuity - Raus, Mohd. Ikhsan Md.; Supian, Suzaini Harmiruslin; Zolkefley, Mohd Khairul Ikhwan Bin; Aziz, Muhd Eizan Shafiq Abd (Springer, 2019)
The socioeconomic challenges caused by aging populations have encouraged many countries to reevaluate the place of the elderly in society as well as to adopt measures in encouraging them to be participative. In recent decades, crowdsourcing has been identified as a rapid growth of innovative Internet-based information and communication technologies in giving the opportunities to educational organizations to reach their goals. With their accumulated skills and knowledge, academic retirees can be resourceful to society. However, their knowledge and experiences seem to be undervalued and underutilized. Retired academics have better opportunity to extend their contribution in the society as their valuable knowledge is more appreciated than people from other background. Retired academics tend to be able to fulfill their desire for professional continuity following retirement more markedly than people from other backgrounds. This paper analyzes the use of crowdsourcing in educational activities, especially for the academic retirees. Therefore, the objectives of this paper are to take an exploratory look on how educational organizations use crowdsourcing as part of their activities at the present time, and to suggest how the practice of crowdsourcing may expand to other educational activities in future.
Keywords: Asie; Réservé UdeM